Self-sufficient power plant prototype composed by cascaded disruptive power units doing work by isothermal contraction and expansion (JOURNAL OF ADVANCES IN PHYSICS, 2024)
This research work aims at the design and development of a disruptive prototype for a Self-sufficient power plant (SSPP) prototype composed by cascaded disruptive power units (PUs) doing work by isothermal contraction-expansion processes. The innovative design integrates thermo-hydraulic actuators enabled to drive hydraulic pumps connected to a hydraulic motor-generator. The prototype's cascaded PUs operates on a double closed processes-based isochoric-isothermal-isochoric-isothermal (VTVT) thermal cycle, enabled to do useful work by contraction and expansion of a thermal working fluid (TWF), which is notable for its high specific work output and high thermal efficiency. This is due to a disruptive cascaded heat recovering technique associated to a heat upgrading strategy.Among the most relevant Key Features are its self-sufficient operation modes that challenge traditional limitations of second-kind perpetual motion machines (PMMs)The expected capabilities on the basis of the consistency of empirical analysis are summarized as:- Design based on the optimal number of cascaded power units,- Efficient generation of useful mechanical work through expansion and contraction of the TWF,- High specific useful work (kJ/kg of TWF), such as helium,- Low ratio of actuator volume and weight to specific work.Preliminary tentative validation:The prototype design model was validated through case studies using air and helium as real TWFs. Empirical results demonstrate the SSPP's exceptional performance under certain conditional restrictions. - The optimal SSPP completed with nine cascaded PUs each operating on a double-VTVT cycle per PU.- Helium: RIT value of 0.9 and 9 PUs coupled in cascade to give an SSI of 156.72and a SSEP yield of 922.23 kJ/kg.cy.- Air: RIT value of 0.9 and 9 PUs coupled in a shell to give an SSI of 27.41 and a SSEP production of 37.67 kJ/kg.cy. These findings highlight the prototype's potential to significantly advance energy production efficiency and self-sufficiency in power generation systems.